(untitled) (ModaPalavra e-periódico, 2015)
For with the advancement of societies and digital technology media have become the fashionstage. This article to Investigate the digital communication Antix (Brazilian brand of women’s clothing) concerns the study to analyze power relations q the mark has to be noise on social networks like Facebook and Instagram. It is understood the current movement is giving increased access to the catwalk fashion and everything relates to the process of creation and development of collections beyond culture and social movement. The power relationshipthe brand has is included in this advent of digital medium. With new technological supports the brand has established itself in the fashion market and garments have Become objects of desire of many women.